Capital Accounting Based on Local Cultural Values by Gorontalo Travelers to Mecca - Thalib, Mohamad Anwar; Mohamad, Roni (Institut Agama Islam Negeri Ponorogo, 2025)
This study aims to understand the capital accounting practices of travelers from Gorontalo to Mecca using bicycles based on local cultural values. This study is positioned within the Islamic paradigm using an Islamic ethno-methodology approach. The data analysis method consisted of five stages: charity, knowledge, faith, revelation-based information, and courtesy. The findings show that the primary sources of capital are merchandise sales and support from friends and fellow Muslims. This capital is used to finance travel necessities, including food, accommodation, and bicycle repairs, as well as charity throughout the journey. In practice, initial capital recording was done in writing, but as the journey progressed, financial records were retained only in memory. This reflects a non-material value-based accounting concept in which the belief in sustenance predestined by the Creator serves as the primary foundation for financial management. Additionally, in Gorontalo’s Islamic culture, this belief is reflected in the phrase Diila o, onto, bo wolu-woluwo, meaning